Effective Houses Property Rights and Settlement in Iron Age Eastern Norway - Gjerpe, Lars Erik (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
This book examines property rights, settlement structure and social organization in Norway's Østlandet in the Iron age (500 BC-AD 1050). Inspired by ethnographical and anthropological studies, a model of a stateless, agrarian and hierarchical society with socially based rights to land is presented. In this model, where there are no territorially embedded rights, society is better represented as a heterarchy or anarchy than as a hierarchy. Power in society was shared between the honoured warrior, the powerless leader and perhaps also the productive farmer. This model differs from that presented by standard Norwegian research, where the retrogressive method is combined with a belief in the stability and continuity of the farm. A critical study of Norwegian research history is therefore an essential part of this book. This study has also been able to make use of new and extensive settlement evidence gained from machine-stripping of topsoil from large areas in the past thirty years; this has shed new light on the issues discussed in the book related to building practices and the settlement pattern.